A robust ex vivo method to evaluate the diffusion properties of agents in biological tissues. Issue 4 (10th January 2019) - Carneiro, Isa; Carvalho, Sónia; Henrique, Rui; Oliveira, Luís M.; Tuchin, Valery V.
Abstract : A robust method is presented for evaluating the diffusion properties of chemicals in ex vivo biological tissues. Using this method that relies only on thickness and collimated transmittance measurements, the diffusion properties of glycerol, fructose, polypropylene glycol and water in muscle tissues were evaluated. Amongst other results, the diffusion coefficient of glycerol in colorectal muscle was estimated with a value of 3.3 × 10 −7 cm 2 /s. Due to the robustness and simplicity of the method, it can be used in other fields of biomedical engineering, namely in organ cryoprotection and food industry. Abstract : The determination of the diffusion properties of chemicals in biological materials has great interest in clinical practice, dermatology, pharmacology, cryogenics or in food industry. Using the optical clearing technique in muscle tissues, we present a simple and robust ex vivo method, based only on collimated transmittance and thickness measurements that allows the estimation of the diffusion time and diffusion coefficient of various agents.